The mechanism of hydrazine electro-oxidation revealed by platinum microelectrodes: role of residual oxides. - Aldous, L; Compton, R (2011)
The electrochemistry of hydrazine at platinum has been re-evaluated by an investigation using microelectrodes. Platinum oxides remaining from preceding oxidative scans results in hydrazine oxidation occurring up to ca. 400 mV more cathodic than at an oxide-free Pt electrode. The observed voltammetry at oxidised or 'activated' platinum electrodes was found to be a function of the immersion time (time since 'activation') and pH. Differences between phosphate, sulphate and acetate-based electrolytes are noted. The anodic hydrazine oxidation features at 'activated' electrodes occurred as a prewave or a prepeak, depending upon the electrolyte and scan rate employed. Although hydrazine is known to react with bulk Pt oxide, the loss of activation with time was found to be independent of hydrazine concentration and was instead a function of pH and supporting electrolyte, therefore the 'activation' corresponds to residual rather than bulk platinum oxide. The condition of platinum was examined by X-ray photoelectron spectroscopy (XPS), which demonstrated an increase in oxygen coverage with cycling and the absence of any strongly adsorbed or poisoning species. The facile oxidation of hydrazine has implications with regards to hydrogen storage, generation and fuel cells. The different effects corresponding to insufficient buffering, which has relevance to the electroanalytical detection of hydrazine, was also investigated.